Personal Construction of Cough Medicine among Young Substance Abusers in Hong Kong - Daniel T. L. Shek (The Scientific World Journal)
Although cough medicine abuse is a growing problem in many places, there is no study examining the views of young substance abusers toward cough medicine. The objective of this study was to examine personal constructions of cough medicine abusers via the repertory grid tests (𝑁=11). Several observations are highlighted from the study. First, personal constructions of cough medicine were mixed, including the benefits and harmful effects of its abuse. Second, although the informants perceived cough medicine to be addictive and harmful, they perceived cough medicine to be less addictive and less harmful than did heroin. Third, while the informants construed cough medicine to be similar to ketamine and marijuana, they also perceived cough medicine to possess some characteristics of heroin. Fourth, relative to the construed similarity between heroin and the gateway drugs (cigarette, beer, and liquor), the informants construed cough medicine to be more similar to the gateway drugs. Finally, a higher level of perceived dissimilarity between cough medicine and gateway drugs was related to a higher level of perceived harm of cough medicine abuse.